2004
DOI: 10.1080/14766080409518542
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Discernment: An Examination in the Case of Employee Appraisal

Abstract: We present a preliminary investigation of the concept of managerial discernment. Discernment provides managers with a structured process invoking both the rationality and the spirituality of the decision-maker in order to improve decision quality. First we introduce the core concepts, using Ignatian discernment as a basis. Second, we illustrate managerial discernment using an actual case of employee appraisal, combined with a simulation based on the information obtained from the case. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Thus, for example, extant research has found an overlap between individual and organizational values (beliefs) that may be considered spiritual, as concerns the establishment of trust (Li, Bai & Xi, 2011), and of normative behaviour, as concerns propensity for innovation (Assouad & Parboteeah, 2018). With the inroads that the study of spirituality and religion has made into organization studies, we find, at one end, scholarship on specific faith aspects of organizational life, such as the deployment of industrial chaplains at the workplace (Wolf & Feldbauer-Durstmüller, 2018), and at the other end, the import of religious practice into organizational life, like mindfulness (Vu & Gill, 2018) and discernment (Falque & Duriau, 2004). Leadership, perhaps the most studied aspect of management in organizations, has seen the development of new constructs such as spiritual leadership (Fry, 2003) and servant leadership (Van Dierendonck, 2011), as well as inputs from the realm of spirituality/religion into extant constructs, such as transformational leadership (Pravichai & Ariyabuddhiphongs, 2018).…”
Section: Spirituality and Religionmentioning
confidence: 99%
“…Thus, for example, extant research has found an overlap between individual and organizational values (beliefs) that may be considered spiritual, as concerns the establishment of trust (Li, Bai & Xi, 2011), and of normative behaviour, as concerns propensity for innovation (Assouad & Parboteeah, 2018). With the inroads that the study of spirituality and religion has made into organization studies, we find, at one end, scholarship on specific faith aspects of organizational life, such as the deployment of industrial chaplains at the workplace (Wolf & Feldbauer-Durstmüller, 2018), and at the other end, the import of religious practice into organizational life, like mindfulness (Vu & Gill, 2018) and discernment (Falque & Duriau, 2004). Leadership, perhaps the most studied aspect of management in organizations, has seen the development of new constructs such as spiritual leadership (Fry, 2003) and servant leadership (Van Dierendonck, 2011), as well as inputs from the realm of spirituality/religion into extant constructs, such as transformational leadership (Pravichai & Ariyabuddhiphongs, 2018).…”
Section: Spirituality and Religionmentioning
confidence: 99%
“…The phenomenon of discernment continues to gain traction in management and organization studies (Allen, 2017; Benefiel, 2008; Delbecq et al, 2004; Falque and Duriau, 2004; Miller, 2020; Vu and Burton, 2020). Discernment has primarily been explored as an approach to decision-making that integrates emotions, feelings and perceptions, with practical wisdom drawn from spiritual and religious traditions (Miller, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent literature review, Miller (2020) charted the chronological development of the field and noted that there is no unified or single concept of discernment and that different processes of discernment occur across different traditions. Two religious traditions characterize much of this body of work – the Ignatian tradition of individual discernment (Cavanagh and Hazen, 2008; Falque and Duriau, 2004) and the Quaker tradition of collective discernment (Allen, 2017; Burton and Bainbridge, 2019; Burton and Sinnicks, 2021; Reis Louis, 1994). However, while there are differences between their individual and collective foci, each shares a distinctive integration of concerns for the social world and an inwardness that draws from the normative and ethical commitments of the particular discerning community.…”
Section: Introductionmentioning
confidence: 99%